A History of Penicillin: The Miracle of Medicine - Rogers, John P. (Kansas State University. Dept. of History, 2017)
The discovery of penicillin in 1928 was a breakthrough in the world of medicine. Bacterial diseases could now be treated rapidly and easily without the long, complex regimens prescribed by doctors before this time. Surprisingly, many in the public and medical communities accepted this new medicine quickly with (seemingly) very few skeptics about the application of this newfound medicine. This paper seeks to explain why that happened. Examining not only the discovery of penicillin and its contribution to modern medicine, but also analyzing how doctors treated bacterial diseases before the discovery such as diphtheria will accomplish this goal. These methods serve as a means of hypothesizing why the acceptance of penicillin was so rapid. The analysis will be accomplished using newspaper articles and medical journals from mainly the 19th and 20th centuries, using secondary sources only to supplement what cannot be found in the available sources.
Keywords: Social medicine; Modern medicine; Alexander Fleming; Discovery of Penicillin; Nineteenth Century Medicine; History of medicine